An Identity Crisis of Architectural Critique. Issue 1 (21st May 2014) - Tsiambaos, Kostas
Abstract : Over the last three years Greece has been facing one of its worst crises since the 1950s, a crisis which most understand to be a financial one. The word crisis (from the Greek κρίσις) has a double meaning in the Greek language. Its first meaning indicates a radical — usually negative — change in the sum of conditions or flow of events, while its second refers to an opinion, a theory, a personal judgment or point of view towards a specific subject. I will argue that the current crisis is not just financial, but deeply cultural. An examination of the history of architectural discourse in Greece will help us better understand the cultural identity of the recent crisis by illuminating its core: the ambivalent relationship between Greece and Europe, from the establishment of the Greek state until today.